2022
DOI: 10.1371/journal.ppat.1010760
|View full text |Cite
|
Sign up to set email alerts
|

PGRS domain structures: Doomed to sail the mycomembrane

Abstract: The impact of artificial intelligence (AI) in understanding biological processes is potentially immense. Structural elucidation of mycobacterial PE_PGRS is sustenance to unveil the role of these enigmatic proteins. We propose a PGRS “sailing” model as a smart tool to diffuse along the mycomembrane, to expose structural motifs for host interactions, and/or to ship functional protein modules at their C-terminus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…PG II sandwiches are formed by left-handed antiparallel PG II helices, sharing a similar conformation as poly-proline II [12,13], albeit stacked in two antiparallel groups, with glycine always pointing inwards, where no other residue would fit. More recently, the availability of AlphaFold2.0 offered a unique opportunity to better understand structural and functional properties of these sibylline domains [14]. Consistent with our previous models, AlphaFold2.0 predicts the structure of PGRS as PG II sandwich domains of modular size, with a large variability in the number of constituting PG II helices.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…PG II sandwiches are formed by left-handed antiparallel PG II helices, sharing a similar conformation as poly-proline II [12,13], albeit stacked in two antiparallel groups, with glycine always pointing inwards, where no other residue would fit. More recently, the availability of AlphaFold2.0 offered a unique opportunity to better understand structural and functional properties of these sibylline domains [14]. Consistent with our previous models, AlphaFold2.0 predicts the structure of PGRS as PG II sandwich domains of modular size, with a large variability in the number of constituting PG II helices.…”
Section: Introductionsupporting
confidence: 80%
“…Consistent with previous data, all modelled structures present a PE domain with an αhelical conformation, followed by the PGRS domain. Between the two domains, and conserved in the entire family, is the GRPLI motif (Figure 1) [5,14].…”
Section: Main Distinctive Features Of Pe_pgrs Structuresmentioning
confidence: 99%
“…Indeed, PE_PGRS33 interaction with Toll-like receptor 2 (TLR2) promotes the secretion of inflammatory chemokines and cytokines, which are key in the immunopathogenesis of tuberculosis [ 4 ]. This study, corroborated by successive studies [ 5 ], suggested that the PGRS domain of PE_PGRS33 exposes PGII sandwich domains on the outer surface, which are involved in the interactions with the host receptors [ 4 ]. As such, they are promising targets for a vaccination strategy aimed at inducing a humoral response.…”
supporting
confidence: 74%
“…Many of these belong to the 'Tetratricopeptide-like helical domain superfamily' where the median PDB structure length of structures with resolution < 3Å is only 370. Another example of repetitive structural outliers which are thought to be novel folds include the unusual "PGRS domains", found widely in mycobacteria (Berisio and Delogu, 2022).…”
Section: Fragments Repeats and Obligate Complexesmentioning
confidence: 99%